Methodology of collaborative learning through ICT: an approach to the professors and students opinions - García-Valcárcel Muñoz-Repiso, Ana; Hernández Martín, Azucena; Recamán Payo, Adriana (Revista Complutense de Educación, 2012)
The current learning theories recognize the importance of social relationships and interaction with others in the acquisition of knowledge; the ability to work in groups to achieve common goals appears as a cross-curricular learning in all educational levels. In addition, digital technologies are in a process of expansion and generalization in educational systems, which enables the communication between students and professors all around the world. This fact contributes to the creation of social environments for interaction, what combined in Web 2.0 applications, makes up appropriate instruments to explore new methodological approaches and encourage existing ones. All of this explains why collaborative learning methods through ICT is rapidly gaining importance and scope in educational innovation. The paper presents the teachers and students opinions, which were given through a questionnaire, about the potentiality of collaborative learning and their experiences in this field. TIC expectations to improve this kind of learning are very optimistic.